An international CAPM for partially integrated markets: Theory and empirical evidence - Arouri, Mohamed El Hedi; Nguyen, Duc Khuong; Pukthuanthong, Kuntara (Journal of Banking & Finance, 2012)
This article proposes a theoretical testable capital asset pricing model for partially segmented markets. We establish that if some investors do not hold all international assets because of direct and/or indirect barriers, the world market portfolio is not efficient and the traditional international CAPM must be augmented by a new factor reflecting the local risk undiversifiable internationally. We also introduce a suitable framework to test this model empirically. Using a sample of six emerging markets and three mature markets, we find that the degree of stock market integration varies through time and that most of the sample emerging markets have become more integrated in the recent years. The local risk premium for emerging markets represents the most important component of the total risk premium, but its relative importance has decreased recently. Differently, the total risk premium for developed countries is largely driven by global factors.